Trans narratives on school experiences—This is how we feel - Etxebarria-Perez-de-Nanclares, Olatz; Vizcarra Morales, Maria Teresa; López-Vélez, Ana Luisa; Gamito Gómez, Rakel (Frontiers in psychology, 2024)
The school environment remains unsafe for many trans people, where they are victims of discrimination, aggression, and bullying, resulting in socioemotional and physical harm to trans individuals. Intersectionality and minority stress are contributing factors in this already challenging education environment. In many cases, the voices of trans people are not heard or listened to at school; therefore, this study aims to listen to their school experiences in order to identify key areas for improvement. This study implemented a narrative research approach where six in-depth interviews were completed with trans participants from the Basque Country, Europe, and the United States of America that focused on five dimensions: being a trans, the role of school, lack of teacher education and training, segregation by gender, and socioemotional wellbeing. The transcriptions of these interviews were coded using Nvivo software in categorical systems in a deductive and inductive way. The results clearly showed that the binary society has a negative impact on trans people. In addition, the educational environment is still hostile for most of them, in which the lack of teacher training and gender identity content in the curriculum has a negative impact on trans people and their experiences at school. The findings support the idea that socially ingrained binarism is detrimental to all those who step outside the norm. It can also be said that the earlier the transition is made, the better the effect (clinical as well as socioemotional) on their personal lives. For this early transition to occur, it is necessary to have access to information from an early age.